Perlindungan Hukum Bagi Janda atau Duda dalam Wasiat Pemilik Harta Bersama Terkait Akta Waris Notaris - Ramdani, Siti Rahmaniar (Postgraduate of Jayabaya University, 2023)
Joint property refers to assets acquired during a marriage, signifying partial ownership held by both the husband and the wife. Marital assets, as defined in Article 35, Paragraph (1) of the Marriage Law No. 1 of 1974, state: 'Property acquired during the marriage becomes joint property.' Consequently, the inheritance assets for a deceased husband or wife that can be inherited encompass a portion of their joint property. However, a phenomenon observed within society involves the inclusion of widows or widowers in wills, followed by the subsequent distribution of these assets among heirs or beneficiaries. The methodology employed for this research is of the normative juridical type, specifically library-based legal research. Various research approaches are adopted, including the Legislative Approach, Case Approach, Conceptual Approach, and Analytical Approach. Techniques such as legal interpretation, grammatical interpretation, systematic interpretation, teleological interpretation, and legal construction methods are utilized to analyze legal materials. The findings of this research reveal the following outcomes: (1) The Legal Consequences of Testamentary Instruments and Inheritance Right Certificates do not come into effect due to their annulment by the Court. However, sanctions are imposed on Notaries for creating Testamentary Instruments and Inheritance Right Certificates pertaining to the portion of assets belonging to widows or widowers, which are incorporated within the ambit of the beneficiaries. (2) Legal protection for widows/widowers concerning their share of communal assets is aligned with Article 35, Paragraph (1) of Law No. 1 of 1974 on marriage, which states, 'Property obtained during the marriage becomes joint property.' Thus, widows/widowers retain the right to claim a portion of their joint assets. Through the principle of Hereditatis Petitio as per Article 834 of the Civil Code, every heir is entitled to pursue legal actions to safeguard their inheritance rights.